Pengaruh Penambahan Natrium Borax Tetra Hydrate dan Diammonium Phosphate Terhadap Kuat Tekan Geopolimer - Egalita Islami Bilqis; Wiwik Dwi Pratiwi; Rizal Indrawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
Geopolymers are solid inorganic polymers produced from a chemical reaction called geopolymerization between an alkaline solution and an aluminosilicate source. Aluminosilicate materials are composed of silica and alumina atoms. To activate the polymerization reaction between silica (Si) and alumina (Al) an activator solution is needed. Many studies have used geopolymers because they are known for their fire retardant properties. With the added ingredients of Sodium Borax Tetra Hydrate and Diammonium Phosphate, these two added ingredients have the potential to be fire retardants. To determine the effect of the addition of geopolymer additives, pressure testing was carried out on the specimens before and after being burned at 900 oC for 1 hour. In this study, using raw materials metakaolin and silica fume of 80:20 (%) and a constant KOH pellet and water glass activator solution. As well as varying the additives, namely 1% Sodium Borax Tetra Hydrate, 1% Diammonium Phosphate and specimens without additives. The results of the compression test showed that the composition that had the best compressive strength before combustion was the addition of 1% Diammonium Phosphate, which was 24.4 MPa. While the specimens after burning which have the highest compressive strength value are the specimens without additives, namely 9.5 MPa.